2022
DOI: 10.1136/bmjopen-2021-049540
|View full text |Cite
|
Sign up to set email alerts
|

Development of chronic kidney disease influenced by serum urate and body mass index based on young-to-middle-aged Japanese men: a propensity score-matched cohort study

Abstract: ObjectiveTo investigate the association between serum uric acid (SUA) level and body mass index (BMI) on the development of chronic kidney disease (CKD) in working men aged 20–60 years.DesignRetrospective cohort study.SettingData from employees’ annual health check-ups were collected from two companies in 2009 and 2014.ParticipantsA total of 16 708 working men were recruited. We excluded participants with missing essential data (N=7801), who had basal estimated glomerular filtration rate (eGFR) <60.0 mL/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…To describe the non-equivalence of our cohort, we performed propensity score matching with logistic regression (SAS version 9.2, SAS Institute Inc., NC, USA) 43 , 44 . The cohort was formed based on 1:1 nearest-neighbor matching using a greedy algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…To describe the non-equivalence of our cohort, we performed propensity score matching with logistic regression (SAS version 9.2, SAS Institute Inc., NC, USA) 43 , 44 . The cohort was formed based on 1:1 nearest-neighbor matching using a greedy algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…One of those studies identified the UA level as an important predictor of CKD [56]. A recent study observed that higher UA levels correlated significantly with CKD in middle-aged men regardless of their BMI [57]. Based on the findings of this study, it was discovered that in longitudinal data, the important variable UA may be more meaningfully assessed through the standard deviation "UA(S)" values of its multiple examinations.…”
Section: Discussionmentioning
confidence: 70%
“…Serum uric acid (SUA), as the final purine metabolite catalyzed by xanthine oxidoreductase (XO), reflects the degree of oxidative stress in vivo ( 12 ). Over the past two decades, numerous epidemiological studies have shown that elevated SUA levels are closely related to various diseases, including hypertension ( 13 ), coronary heart disease ( 14 ), cardiovascular disease ( 15 , 16 ), obesity ( 17 ), diabetes ( 18 ), metabolic syndrome ( 19 ), liver dysfunction ( 20 ), and chronic kidney disease ( 21 ). Moreover, a variety of studies have demonstrated that a high SUA level is significantly associated with AF and may be a potential risk factor for AF ( 22 28 ).…”
Section: Introductionmentioning
confidence: 99%